Adios, Oscar! : a butterfly fable - Elwell, Peter (New York : Blue Sky Press, 2009)
Despite his friends' teasing, Oscar the caterpillar studies to prepare for becoming a butterfly and migrating to Mexico, so when things do not turn out as he expects, he is still able to make his dream come true.
Horn Book.
Kirkus Review.
School Library Journal.
Horn Book, October 2009.
Kirkus Review, March 2009.
Library Media Connection, October 2009.
Keywords: Book-worms -- Juvenile fiction; Books and reading -- Juvenile fiction; Caterpillars -- Juvenile fiction; Individuality -- Juvenile fiction; Moths -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Book-worms -- Fiction; Books and reading -- Fiction; Caterpillars -- Fiction; Identity -- Fiction; Moths -- Fiction; Self-actualization (Psychology) -- Fiction; Book-worms -- Fiction; Books and reading -- Fiction; Caterpillars -- Fiction; Individuality -- Fiction; Moths -- Fiction; Self-realization -- Fiction